Inovasi Pelayanan Publik untuk Meningkatkan Pelayanan Kependudukan di Kota Surabaya - Wibowo, Cahyo Bima Sakti (Universitas Airlangga, 2020)
Abstract This study aims to describe the quality of public services using the approach of Zeithaml, Berry, and Parasuraman. The City of Surabaya through the Department of Population and Civil Registration of the City of Surabaya made an electronic